The Description Of Diabetics’ Acceptance Stage Toward Diabetes Mellitus’ Diagnoses - Ana Nistiandani; Achmad Zulfa Juniarto; Niken Safitri Dyan (Alma Ata University Press, 2018)
Abstract Diabetes Mellitus (DM) is a chronic condition which requires various kinds of lifetime treatment which cause grief. Grief has stages which can be passed though normally with the attainment of acceptance stage. Acceptance attainment renders a description maintaining that grief in its process is undergone normally through uncomplicated grief reaction and emotional responsiveness. A diabetics who manages to attain the acceptance stage will have a better glycemic control, while a diabetics with a low acceptance stage may experience an ineffective coping, improper self-treatment, and distress increase, all of which end up in a bad glycemic control which causes physical complications. This suggests that a description of s’ acceptance stage is important to identify. Accordingly, the aim of this research is to identify and analyze the description of diabetics’ acceptance of DM diagnoses. The method utilized is descriptive-observational, the data collected using the ‘Acceptance of Disease and Impairments Questionnaire’ (ADIQ). The analysis employed in this research is a descriptive analysis. The sampling technique used is consecutive sampling. The research result shows that, based on the diagram of ADIQ administered on 20 s, there are 30% found to be in the stage of acceptance, while there exist 70% to be in the stage of not yet attaining acceptance, which comprises denial (20%), resistance (10%), and sorrow (40%). Failure in attaining the acceptance stage is caused by the s’ still being in the states of denial, resistance, and sorrow. Based on the research result, it can be concluded that the s dominantly stay at the stage of not yet attaining acceptance. The diabetics who have attained acceptance may still be exposed to the risk of undergoing a maladaptive response which may trigger depression, anxiety, worsened physical health, self-treatment discontinuation, powerlessness, low self-esteem, social isolation, even suicidal drive. This is all caused by grief which constitutes a fluctuate condition where every diabetes can contribute to describing his or her condition at every stage. Keywords: stages of grief, acceptance, denial, resistance, sorrow